Bloody olfaction? Confounding associations of sex and age on the influence of blood parameters and body weight on odor identification performance in healthy adults - Schicker, Doris; Karacan, Brid; Brandl, Beate; Skurk, Thomas; Volkert, Dorothee; Hauner, Hans; Freiherr, Jessica (Physiology & behavior, 2022)
Olfactory function and nutrition are closely related and may influence each other via metabolic parameters. However, the relationship between nutritional blood parameters and olfactory performance is still unclear. Inconclusive findings exist for specific blood parameters. In this extensive analysis, we examined the relationship between olfactory performance, measured with MONEX-40, as well as intensity and pleasantness ratings with 38 metabolic blood parameters, age, sex, and the anthropometric measurements body mass index (BMI) and body fat percentage (BFP). Therefore, we included data of 418 healthy, well-phenotyped Caucasians of the Enable cohort. We replicated age-dependent olfactory identification scores (p < 0.001) and found slight evidence for a body fat dependence measured with BFP (BF10 = 10.466). We further identified a sex difference only in middle-aged adults (p < 0.001) that could be explained by environmental factors. Several blood parameters correlated significantly with the MONEX-40 score (p < 0.05 – p < 0.001). However, these effects diminished after adjusting for sex and age (p > 0.9) that were identified as confounders. The same applies for BFP. In addition, no parameters were identified to correlate significantly with perceived olfactory intensity or pleasantness score if controlled for sex and age (p > 0.08). Our results suggest that metabolic blood parameters are not related to olfactory identification performance in a relevant manner and highlight the importance of controlling for sex and age in chemosensory research.
CRIS-Team Scopus Importer:2022-08-19
Keywords: Age; Blood parameter; Body weight; Nutrition; Olfaction; Sex

Measurement of Stress Relief during Scented Cosmetic Product Application Using a Mood Questionnaire, Stress Hormone Levels and Brain Activation - Springer, Arielle; Hoeckmeier, Laura; Schicker, Doris; Hettwer, Stefan; Freiherr, Jessica (Cosmetics, 2022)
Nowadays, consumers’ well-being plays a decisive role in the purchase of cosmetic products. Although factors influencing consumers’ well-being are very subjective, companies strive to develop their products in such a way that a positive effect is likely. Therefore, methods are required to objectively explore and scientifically prove the product’s performance on humans. In this placebo-controlled study, a method was developed to evaluate relaxation or stress relief associated with one olfactory ingredient of a cosmetic product (face cream). Our experimental protocol included product testing in 25 healthy females, while an emotion questionnaire, analysis of saliva samples regarding the concentration of the hormones cortisol and α-amylase and mobile EEG measurement for quantification of the alpha brain waves before and after stress induction were conducted. It was shown that with this experimental design, the sample with the ingredient produced significant stress relief, as evidenced by significantly less negative emotion, significantly lowered cortisol levels and showed a trend towards a significant increase in alpha activity compared to placebo application. Our data provide evidence that this method is suitable for analyzing the differences between the two samples. In the future, this method can be utilized in the current or a further optimized form to evaluate the psychophysiological effects of cosmetic products on humans.
CRIS-Team Scopus Importer:2022-11-04
Keywords: alpha waves; amylase; aroma; brain activity; cortisol; EEG; fragrance; neuroscience; positive mood; relaxation; scent; skin care; well-being

Nutrition claims influence expectations about food attributes, attenuate activity in reward-associated brain regions during tasting, but do not impact pleasantness - Rramani, Qendresa; Barakat, Youssef; Jacob, George; Ohla, Kathrin; Lim, Shirley Xue Li; Schicker, Doris; Freiherr, Jessica; Saruco, Elodie; Pleger, Burkhard; Weber, Bernd; Schultz, Johannes (Brain and Behavior, 2022)
IntroductionNutrition claims are one of the most common tools used to improve food decisions. Previous research has shown that nutrition claims impact expectations; however, their effects on perceived pleasantness, valuation, and their neural correlates are not well understood. These claims may have both intended and unintended effects on food perception and valuation, which may compromise their effect on food decisions. MethodsWe investigated the effects of nutrition claims on expectations, perceptions, and valuation of milk-mix drinks in a behavioral (n = 110) and an fMRI (n = 39) study. In the behavioral study, we assessed the effects of a "fat-reduced" and a "protein-rich" nutrition claim on expected and perceived food attributes of otherwise equal food products. In the fMRI study, we investigated the effect of a "protein-rich" claim on taste pleasantness perception and valuation, and on their neural correlates during tasting and swallowing. ResultsWe found that both nutrition claims increased expected and perceived healthiness and decreased expected but not perceived taste pleasantness. The "protein-rich" claim increased expected but not perceived satiating quality ratings, while the "fat-reduced" claim decreased both expected and perceived satiating quality ratings. In the absence vs. presence of the "protein-rich" claim, we observed an increased activity in a cluster extending to the left nucleus accumbens during tasting and an increased functional connectivity between this cluster and a cluster in right middle frontal gyrus during swallowing. ConclusionAltogether, we found that nutrition claims impacted expectations and attenuated reward-related responses during tasting but did not negatively affect perceived pleasantness. Our findings support highlighting the presence of nutrients with positive associations and exposure to foods with nutrition claims to increase their acceptance. Our study offers insights that may be valuable in designing and optimizing the use of nutrition claims.
CRIS-Team WoS Importer:2022-12-30